Low-frequency oscillations in human tibial somatosensory evoked potentials Oscilações de baixa freqüência no potencial evocado somato-sensitivo do nervo tibial humano - Carlos Julio Tierra-Criollo; Antonio Fernando Catelli Infantosi (Arquivos de Neuro-Psiquiatria)
Oscillatory cerebral electric activity has been related to sensorial and perceptual-cognitive functions. The aim of this work is to investigate low frequency oscillations (<300 Hz), particularly within the gamma band (30-110 Hz), during tibial stimulation. Twenty-one volunteers were subjected to 5 Hz stimulation by current pulses of 0.2 ms duration and the minimum intensity to provoke involuntary twitch. EEG signals without (spontaneously) and during stimulation were recorded at primary somatosensory area. A time-frequency analysis indicated the effect of the stimulus artifact in the somatosensory evoked potential (SEP) frequencies up to 5 ms after the stimulus. The oscillations up to 100 Hz presented the highest relative power contribution (approximately 99%) for the SEP and showed difference (p<0.01) from the frequencies of the spontaneously EEG average. Moreover, the range 30-58 Hz was identified as the band with the highest contribution for the tibial SEP morphology (p<0.0001). Oscilações da atividade elétrica cerebral têm sido associadas a funções sensoriais, de percepção e de cognição. O presente estudo objetiva investigar as oscilações de baixa freqüência, em particular da banda gama (30-110 Hz), durante estimulação do nervo tibial. Vinte e um voluntários foram estimulados com pulsos de corrente de 0,2 ms, freqüência de 5 Hz e intensidade mínima para produzir o movimento involuntário dos músculos intrínsecos do pé. Sinais EEG espontâneo e durante estimulação foram registrados na área somato-sensitiva primária. A análise tempo-freqüência indicou o efeito do artefato ao estímulo na banda de freqüência do potencial evocado somato-sensitivo (PESS) até aproximadamente 5 ms pós-estímulo. As oscilações até 100 Hz apresentaram maior contribuição relativa de potência ao PESS (aproximadamente 99%) e se mostraram significativamente diferentes (p<0,01) das freqüências da média coerente do EEG espontâneo. Além disso, a banda 30-58 Hz foi identificada como a de maior contribuição à morfologia do PESS do nervo tibial (p<0,0001).